THE MODERATING ROLE OF INFORMATION ASYMMETRY ON EARNINGS PERSISTENCE AND EARNINGS RESPONSE COEFFICIENT - Onasis, Dini; Jasman, Jasman (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
This study examines the effect of earnings persistence on earnings response coefficient with the role of information asymmetry as a moderating variable in strengthening or weakening its effect. The data used comes from the company's financial statements gathered from the Indonesia Stock Exchange website. The samples used are manufacturing companies starting from the 2021-2023 period. This research uses a purposive sampling method. The study results indicate that earnings persistence has a positive effect on the earnings response coefficient (ERC), and information asymmetry is empirically proven to weaken the positive impact of persistence on ERC. This study provides advice to shareholders to encourage management to reduce information asymmetry through increased transparency and disclosure of financial statements. With low information asymmetry, it increases earnings persistence which then provides earnings power as a tool for predicting future earnings which consequently provides an increase in ERC.